A history of European women's work : 1700 to the present - Simonton, Deborah, 1948- (Routledge, 1998)
The paid and unpaid work of women in Europe has been and is hugely diverse - from schools to offices, factories to domestic service, dairies to hospitals and much more. The work patterns have fluctuated in relation to ideological, technological, demographic, economic and familial changes. In A History of European Women's Work, Deborah Simonton draws together recent research, lively personal accounts and statistical evidence to take an overview of trends in women's work from the pre-industrial period to the present. The author discusses the definition of work within and without patriarchal families, the status of work and the skills involved. The book examines local as well as Europe-wide developments, contrasting countries such as Britain, Germany and France. Age, class, and crucially control are defining themes of this panoramic work. Deborah Simonton considers women's own perceptions of work, and its place in their lives, to present a rounded account of the shifting patterns of employment and the continuities which are evident in women's own experience.